Identification of WRKY gene family in Dioscorea opposita Thunb. reveals that DoWRKY71 enhanced the tolerance to cold and ABA stress - Xing,Linan; Zhang,Yanfang; Ge,Mingran; Zhao,Lingmin; Huo,Xiuwen (PeerJ, 2024)
WRKY transcription factors constitute one of the largest plant-specific gene families, regulating various aspects of plant growth, development, physiological processes, and responses to abiotic stresses. This study aimed to comprehensively analyze the WRKY gene family of yam (Dioscorea opposita Thunb.), to understand their expression patterns during the growth and development process and their response to different treatments of yam and analyze the function of DoWRKY71 in detail. A total of 25 DoWRKY genes were identified from the transcriptome of yam, which were divided into six clades (I, IIa, IIc, IId, IIe, III) based on phylogenetic analysis. The analysis of conserved motifs revealed 10 motifs, varying in length from 16 to 50 amino acids. Based on real-time quantitative PCR (qRT-PCR) analysis, DoWRKY genes were expressed at different stages of growth and development and responded differentially to various abiotic stresses. The expression level of DoWRKY71 genes was up-regulated in the early stage and then down-regulated in tuber enlargement. This gene showed responsiveness to cold and abiotic stresses, such as abscisic acid (ABA) and methyl jasmonate (MeJA). Therefore, further study was conducted on this gene. Subcellular localization analysis revealed that the DoWRKY71 protein was localized in the nucleus. Moreover, the overexpression of DoWRKY71 enhanced the cold tolerance of transgenic tobacco and promoted ABA mediated stomatal closure. This study presents the first systematic analysis of the WRKY gene family in yam, offering new insights for studying WRKY transcription factors in yam. The functional study of DoWRKY71 lays theoretical foundation for further exploring the regulatory function of the DoWRKY71 gene in the growth and development related signaling pathway of yam.
Keywords: WRKY gene family; Dioscorea opposita Thunb.; Expression pattern; DoWRKY71; Cold; ABA